2019
DOI: 10.1109/access.2019.2938250
|View full text |Cite
|
Sign up to set email alerts
|

Elastic Wave Modulation in Hollow Metamaterial Beam With Acoustic Black Hole

Abstract: We propose and discuss the elastic wave attenuation of hollow metamaterial beam embedded acoustic black hole. More abundant physical phenomena are given by modal analysis, shows that the band gap of three-dimensional acoustic black hole metamaterial is different from two-dimensional one. Lateral flexural vibrations occurs and make the original first two-dimensional band gap be compressed, and the opening of first three-dimensional band gap are caused by coupling effect between the longitudinal and lateral flex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0
2

Year Published

2020
2020
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 86 publications
(18 citation statements)
references
References 32 publications
0
16
0
2
Order By: Relevance
“…In order to simulate the working state of the residential trough solar photovoltaic power supply system, the same type of polysilicon photovoltaic cell module and its matching far-infrared thermal fiber soft board with constant resistance value are used [20]. The technical parameters of polysilicon PV modules used in the impact study are shown in Table 2.…”
Section: Research Scheme Design Of the Influence Of Light Intensity On The Power Generation Performance Of Photovoltaic Cellsmentioning
confidence: 99%
“…In order to simulate the working state of the residential trough solar photovoltaic power supply system, the same type of polysilicon photovoltaic cell module and its matching far-infrared thermal fiber soft board with constant resistance value are used [20]. The technical parameters of polysilicon PV modules used in the impact study are shown in Table 2.…”
Section: Research Scheme Design Of the Influence Of Light Intensity On The Power Generation Performance Of Photovoltaic Cellsmentioning
confidence: 99%
“…In the complex geological environment, the proposed research method of fault diagnosis mechanism is more stable, which improves the reliability of diagnosis results and provides more perfect technical means for the development of national mining technology (Gao et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Most of them only care about development, regardless of the carrying capacity of the ecological environment, only the current development, but not sustainable development and they have the idea of development first, then governance. The scientific development concept must be used to coordinate energy development and ecological protection (Gao et al, 2019).…”
Section: Coordinate Energy Development and Ecological Protection With A Scientific Development Conceptmentioning
confidence: 99%